IMPLEMENTASI UU NO. 14 TAHUN 2008 TENTANG KETERBUKAAN INFORMASI PUBLIK (KIP) PADA PEJABAT PENGELOLA INFORMASI DAN DOKUMENTASI (PPID) KOTA PARIAMAN - Angga Perdana; Asrinaldi Asrinaldi; Asmawi Asmawi (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2018)
This study examines the implementation of Law No. 14 of 2008 concerning Public Information Openness in the Pariaman City Information and Documentation Management (PPID) Officer and the factors that influence it. The implementation of wisdom in this study uses the Edward III policy implementation model which consists of four variables, namely communication, resources, disposition and bureaucratic structure. The results showed that the Pariaman City PPID in carrying out the mandate of Law 14 of 2008 concerning KIP did not run optimally, although in terms of regulations and implementation guidelines (SOP) already had complete guidelines, information services were still limited to the use of external media in the form of magazines. print and electronic media and the use of government website media that have not been compiled according to the KIP Act. The implementation of the UU KIP has not been optimal due to policy communication related to the promotion of understanding that has not been maximally maximized for PPID members, the availability of human resources and budgetary resources also has an impact on the attitude of the implementing apparatus in carrying out their main tasks and functions. Standard in standardizing the standards applied, but existing SOPs have not been applied in the practice of public information disclosure.